2006
DOI: 10.18474/0749-8004-41.2.107
|View full text |Cite
|
Sign up to set email alerts
|

Use of Entomopathogenic Nematodes (Steinernematidae) in Conjunction with Mulches for Control of Overwintering Codling Moth (Lepidoptera: Tortricidae)

Abstract: Mulches were compared to test their utility for enhancing efficacy of entomopathogenic nematodes (EPNs) applied against over-wintering codling moth, Cydia pomonella (L.), larvae. Compared with bare ground, mulches may enhance control by providing cocooning sites for codling moth larvae and a substrate that is easy to treat, maintains moisture, and enhances nematode activity. Steinernema carpocapsae (Weiser) or S. feltiae (Filipjev) were applied at a rate of 2.5 × 109 infective juveniles (IJs)/ha against cocoon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…The persistence of S. carpocapsae was increased through the use of crop residue to protect the EPNs from environmental extremes (Shapiro, Obrycki, Lewis, Jackson, et al, 1999). Applications of S. carpocapsae and S. feltiae for control of overwintering C. pomonella were greatly enhanced through the addition of wood-chip mulch Lacey, Arthurs, Granatstein, Headrick, and Fritts (2006). Also when investigating control of diapausing C. pomonella using H. zealandica, de Waal, Malan, and Addison (2011) determined differences among various types of mulch with pine wood shavings being most favorable.…”
Section: Improved Methods Of Applicationmentioning
confidence: 99%
“…The persistence of S. carpocapsae was increased through the use of crop residue to protect the EPNs from environmental extremes (Shapiro, Obrycki, Lewis, Jackson, et al, 1999). Applications of S. carpocapsae and S. feltiae for control of overwintering C. pomonella were greatly enhanced through the addition of wood-chip mulch Lacey, Arthurs, Granatstein, Headrick, and Fritts (2006). Also when investigating control of diapausing C. pomonella using H. zealandica, de Waal, Malan, and Addison (2011) determined differences among various types of mulch with pine wood shavings being most favorable.…”
Section: Improved Methods Of Applicationmentioning
confidence: 99%
“…These include pheromone-based mating disruption of codling moth via Isomate, codling moth larvae capture using larval aggregation pheromones (Judd and Gardiner 2005) or codling moth population reduction via weekly sprays of granulosis virus (Cossentine and Jensen 2004). Entomopathogenic nematodes can also be used to control overwintering codling moth larvae (Lacey et al 2006a), with efficacy being greater with organic mulch than with bare soil (Lacey et al 2006b). Leafroll caterpillar (Lepidoptera: Tortricidae) larvae can be controlled with the organic microbial pesticide Bacillus thuringiensis Berliner (Bt) (Cossentine et al 2003).…”
Section: Insect Managementmentioning
confidence: 99%
“…Several studies have noted the importance of maintaining moisture for DJs survival and infectivity (Kaya et al 1984;Nachtigall and Dickler 1992;Lacey and Unruh 1998;Unruh and Lacey 2001;Lacey et al 2006a). Lacey et al (2006b) have reported effective control of codling moth when combining irrigation and mulch to extend the survival of DJs. Thus irrigation and mulching the orchard is a possibility to increase EPNs efficacy.…”
Section: Discussionmentioning
confidence: 99%